Needs, rationale, and outcomes of leadership education in neurosurgery - Janissardhar Skulsampaopol; Sylvia Shitsama; Yu Ming; Ake Hansasuta; Michael D. Cusimano (PLoS ONE, 2025)
Background Surgeons are expected to lead teams/organizations to achieve optimal patient outcomes; however, few receive formal education in leadership. The goals of the study were to: 1) assess the unmet needs and gaps in leadership education for neurosurgeons and residents/fellows; 2) identify factors associated with availability of leadership education, access to leadership positions and the similarities/differences across geographic regions and institutional type; 3) describe the associations between gender and leadership; 4) determine the impact of leadership education. Methods International survey of 657 neurosurgeons, residents/fellows. A series of univariate analysis and multivariate were conducted to assess the association between specific variables and leadership outcomes. Results Almost half (48%) indicated that leadership education did not exist in their organization. This lack was more notable in non-academic centers (p < 0.001), among neurosurgeons with less than 5 years of work experience (p = 0.03), and respondents from South America (p = 0.02). Nearly two-thirds (61.1%) reported never having leadership training. Significantly fewer respondents in the age range 35–44 years old (p = 0.02), those working in the Middle East (p = 0.02), neurosurgeons with work experience less than 5 years (p = 0.004), working in non-academic center (p = 0.02) attended leadership training. In contrast to the differences seen across geographic regions and types of institutions, overall, the proportions of males and females having access to leadership training and being offered leadership positions were similar. Among participants, 87.1% of those with leadership training were offered leadership roles, compared to 65.5% of those without leadership training (p <  0.001). Additionally, participants with leadership training experienced a burnout rate of 29.2%, whereas those without leadership training had a higher rate of burnout of 40.5% (p =  0.02). Conclusions There is a pressing need to develop educational opportunities for leadership in neurosurgery, especially for younger neurosurgeons, neurosurgeons working in non-academic centers, in countries and non-academic institutions where leadership education is less accessible. Leadership education is associated with increased numbers of neurosurgical leaders at all levels as well as reduced levels of burnout.